Investigation of Hexagonal Mesoporous Silica-Supported Composites for Trace Moisture Adsorption - Li, Li (Nanoscale Res Lett, 2015)
Moisture control is an important part of effective maintenance program for gas-insulated switchgear (GIS). Herein, hexagonal mesoporous silica (HMS) materials were synthesized by adopting dodecylamine as a structure directing agent, which was then employed as a host for supporting polyethylenimine (PEI) without further calcinations or extraction treatment. The physicochemical properties of the silica support and composites were characterized, and the moisture adsorption capacity of these composites was determined. The reserved template agents resulted in a dramatic improvement in moisture adsorption amount. Among them, 50PEI/DHMS showed the highest adsorption value. The enhanced adsorption could be attributed to the generated hydrogen bonding between amino groups and H(2)O molecules and the improved diffusion of moisture into the bulk networks of PEI polymers due to its better spatial dispersion imposed by the long alkyl chains of template agents, which was confirmed by thermogravimetry results and hydrogen efficiency analysis. Moreover, the maintained terminal amino groups of templates could also function as active sites for moisture adsorption. The results herein imply that the PEI/DHMS composites could be appealing materials for capturing moisture in GIS.